A pilot study of the flipped classroom approach in higher education - Almazán Ruiz, Encarnación; Fuentes Martínez, Raquel (Huarte de San Juan. Filología y Didáctica de la Lengua, 2020)
Teaching and learning grammar have become arduous tasks in the English classroom. On the one hand, students feel they are studying the same topics repeatedly. Teachers, on the other one, think students are not able to acquire the grammatical contents of the syllabus. As a direct consequence, it can be assumed it is high time to change the traditional methodology and introduce new approaches which allow us to involve students in their learning process. This paper is aimed at demonstrating the effectiveness of using the flipped classroom approach when teaching grammar. As it is a learner-centred model, students actively expose to contents at home and the in-class time is used to do tasks related to the previously worked contents. The instrument employed for this study is a questionnaire designed to know students’ opinion about a flipped experience implemented in the English classroom. The results show that this teaching model can be a good option to avoid students’ demotivation when teaching English grammar.